Abscisic acid is required for exodermal suberization to form a barrier to radial oxygen loss in the adventitious roots of rice (Oryza sativa). Issue 2 (1st November 2021) - Shiono, Katsuhiro; Yoshikawa, Marina; Kreszies, Tino; Yamada, Sumiyo; Hojo, Yuko; Matsuura, Takakazu; Mori, Izumi C.; Schreiber, Lukas; Yoshioka, Toshihito
Summary: To acclimate to waterlogged conditions, wetland plants form a barrier to radial oxygen loss (ROL) that can enhance oxygen transport to the root apex. We hypothesized that one or more hormones are involved in the induction of the barrier and searched for such hormones in rice. We previously identified 98 genes that were tissue‐specifically upregulated during ROL barrier formation in rice. The Rice XPro database showed that most of these genes were highly enhanced by exogenous abscisic acid (ABA). We then examined the effect of ABA on ROL barrier formation by using an ABA biosynthesis inhibitor (fluridone, FLU), by applying exogenous ABA and by examining a mutant with a defective ABA biosynthesis gene ( osaba1 ). FLU suppressed barrier formation in a stagnant solution that mimics waterlogged soil. Under aerobic conditions, rice does not naturally form a barrier, but 24 h of ABA treatment induced barrier formation. osaba1 did not form a barrier under stagnant conditions, but the application of ABA rescued the barrier. In parallel with ROL barrier formation, suberin lamellae formed in the exodermis. These findings strongly suggest that ABA is an inducer of suberin lamellae formation in the exodermis, resulting in an ROL barrier formation in rice.